(untitled) (Bangladesh Medical Journal, 2021)
Rotavirus is responsible for acute severe watery diarrhoea in young children. Early and rapid detection of rotavirus infection can help to reduce inappropriate administration of antibiotics and has future positive impact on prevention of drug resistance. This cross-sectional study was designed to determine the role of rotaviral antigen detection by ICT from stool sample of acute diarrhoeal children below five years admitted in Sylhet MAG Osmani Medical College Hospital, Sylhet and was carried out in the department of microbiology in collaboration with the department of paediatrics during the period from 1st January to 31st December, 2018. Total 184 children of under five years of age with acute watery diarrhoea were enrolled in this study. Rotaviral antigen was detected by ELISA (Enzyme Linked Immunosorbent Assay) and ICT (Immunochromatographic test) from stool samples. Out of 184 stool samples, rotaviral antigen was found positive in 84 and 86 cases by ICT and ELISA methods, respectively. ICT showed sensitivity of 90.70% and specificity of 93.88% when compared with ELISA. The rotavirus infection was found highest in male children (61.90%) and in age group of 7 to 12 months (51.89%). Considering the importance of rotaviral diarrhoea, rapid detection of rotavirus infection by ICT is essentially needed and should be practiced routinely as it is relatively reliable, easy to perform and cost-effective. It is particularly important in Bangladesh, where diarrhoea is still contributing a significant proportion of mortality and morbidity in under five children. Bangladesh Med J. 2020 Jan; 49 (1): 14-18